Efficacy and safety of vi-tetanus toxoid conjugated typhoid vaccine (PedaTyph™) in Indian children: School based cluster randomized study - Mitra, Monjori; Shah, Nitin; Ghosh, Apurba; Chatterjee, Suparna; Kaur, Iqbal; Bhattacharya, Nisha; Basu, Suparna (Human vaccines & immunotherapeutics, 2016)
Vi polysaccharide typhoid vaccines cannot be used in children <2 years owing to poor immunogenic and T cell independent properties. Conjugate vaccine prepared by binding Vi to tetanus toxoids (Vi-TT) induces protective levels even in children <2 years. We evaluated efficacy and safety following vaccination with a Vi-TT vaccine in children 6 months to 12 years of age. Overall, 1765 subjects were recruited from two registered municipal urban slums of southern Kolkata. Most of the children of the slum dwellers attended the schools in the locality which was selected with permission from the school authority. Schools were randomly divided into vaccinated (Test group) and unvaccinated group (Control group). Children and their siblings of test group received 2-doses of PedaTyph™ vaccine at 6 weeks interval. Control group received vaccines as per national guidelines. Adverse events (AEs) were examined after 30 minutes, 1 month and clinical events were observed till 12 months post-vaccination. Incidence of culture positive typhoid fever in the control group was 1.27% vis-a-vis none in vaccine group during 12 months. In subgroup evaluated for immunogenicity, an antibody titer value of 1.8 EU/ml (95% CI: 1.5 EU/ml, 2.2 EU/ml), 32 EU/ml (95% CI: 27.0 EU/ml, 39.0 EU/ml) and 14 EU/ml (95% CI: 12.0 EU/ml, 17.0 EU/ml) at baseline, 6 weeks and 12 months, respectively was observed. Sero-conversion among the sub-group was 100% after 6 weeks of post-vaccination and 83% after 12 months considering 4-fold rise from baseline. The efficacy of vaccine was 100 % (95% CI: 97.6%, 100%) in the first year of follow-up with minimal AEs post vaccination. Vi conjugate typhoid vaccine conferred 100% protection against typhoid fever in 1765 children 6 months to 12 years of age with high immunogenicity in a subgroup from the vaccine arm.